Industrial enzymology (London, 1996)
This book contains a collected account of current industrial practice in the industrial use of enzymes, several summary indexes, and comparative descriptions of industrially applicable enzyme preparations. It is extended to provide data for use by all types of natural product processing, chemical and pharmaceutical, food and beverage, feed and environmentally concerned industries as well as university research and teaching departments for their current understanding and future development work
Keywords: enzymes - industrial applications